A Puzzling Silence: James 2:24 before the Reformation - Mooney, Christopher (The journal of theological studies, 2020)
Since the Reformation, James 2:24, ‘justified by works and not by faith alone’, has been the source of special controversy within an already contested epistle. But in the patristic and medieval period it was almost entirely unemployed and ignored, despite the widespread use, both approvingly and critically, of the expression sola fide. This article offers a pre-Reformation reception history of James 2:24. It begins with Origen and Augustine’s broader interpretation of James 2, then turns to the key pre-Reformation references to James: the earliest references (fifth-seventh century), Bede the Venerable (eighth), the Glossa Ordinaria (twelfth), Nicholas of Gorran (thirteenth), John Wyclif and Ps-Jan Hus (fourteenth), and Dionysius the Carthusian (fifteenth). Surprisingly, James 2:24 is at times explicitly harmonized with the expression sola fide, and only rarely used to critique it, because most read the Vulgate’s language in James 2:24 (non ex fide tantum) to refer solely to the need for later good works. At the same time, ‘justified by works’ was generally interpreted as referring to a confirmation or manifestation of justification until the scholastic period, when we find the earliest instances of interpreting ‘justified by works’ as a further justification. These results provide a theologically rich historical perspective on the reception of James 2:24 with respect to the development of sola fide and the scholastic interpretation of ‘justified by works’ as a subsequent increase in justification.